Efficacy and safety of Shenfu injection for the treatment of post-acute myocardial infarction heart failure: A systematic review and meta-analysis - Wu, Yanhua; Li, Shuang; Li, Zunjiang; Mo, Zhaofan; Luo, Ziqing; Li, Dongli; Wang, Dawei; Zhu, Wei; Ding, Banghan (Frontiers in Pharmacology, 2022)
Objective: This systematic review and meta-analysis aimed to investigate the adjuvant effect and safety of Shenfu Injection (SFI) in acute myocardial infarction with heart failure (AMI-HF). Methods: Seven databases were searched to identify randomized controlled trials (RCTs) associated with SFI in the treatment of AMI-HF from May 1990 to May 2022. Primary outcomes included total effective rate, left ventricular ejection fraction (LVEF), and secondary outcomes included BNP, NT-proBNP, Heart rate (HR), Cardiac output (CO) and adverse event (AE). The risk of bias evaluation, meta-analysis, subgroup analysis, sensitivity analysis and publication bias were conducted by RevMan5.3 software, and the grade of Recommendations Assessment (GRADE) system was used to evaluate the quality of evidence of meta results. Results: 3231 patients with AMI-HF were included in 36 studies. Meta results suggested that adjuvant SFI therapy was superior to conventional medical therapy alone in patients with AMI-HF. It improved total effective rate (RR = 1.33; 95% CI, (1.25,1.40); P < 0.00001), increased LVEF (SMD = 0.82; 95% CI (0.71, 0.92); P < 0.00001) and decreased HR (SMD = -1.14; 95% CI (-1.28, -0.99); P < 0.00001). In terms of safety, AE rate of adjuvant SFI therapy (9.73%, 66/678) is lower than that of conventional medical therapy (21.7%, 147/677) which indicated that adjuvant SFI therapy is safer (RR =0.45; 95% CI, 0.35, 0.57; P <0.00001). The quality of the evidence for the outcomes were rated from “very low” to “moderate”. Conclusion: SFI combined with conventional medical therapy was safer to improve the total effective rate and improve the heart function of AMI-HF. However, further well-designed RCTs were needed to confirm the efficacy and safety of adjuvant SFI therapy in the treatment of AMIWHF due to the low quality of the evidence for the outcomes.